Recent advancement of cyanobactins and cyanobactin prenyltransferases from 2021 to 2024 - Khan, Abujunaid Habib; Phan, Chin-Soon (Frontiers in Natural Products, 2025)
Macrocyclic compounds have emerged in the 21st century, among which cyclic peptides are of particular interest. Cyanobactins are ribosomally synthesized and post-translationally modified peptides (RiPPs), many of which exist as cyclic peptides with a prenyl moiety, and prenylation can improve their structural stability and biological activity. This mini-review highlights the recently discovered cyanobactins and cyanobactin prenyltransferases from 2021 to 2024. Cyanobactin prenyltransferases will allow access to unique prenylated natural products for applications in drug discovery.